Improved predictive modelling of coralligenous formations in the Greek Seas incorporating large-scale, presence–absence, hydroacoustic data and oceanographic variables - Fakiris, Elias; Dimas, Xenophon; Giannakopoulos, Vasileios; Geraga, Maria; Koutsikopoulos, Constantin; Ferentinos, George; Papatheodorou, George (Frontiers in Marine Science, 2023)
Our understanding of the distribution of coralligenous formations, throughout but mostly on the Eastern Mediterranean seafloor, is still poor and mostly relies on presence-only opportunistic trawling and fishermen reports. Previous efforts to gather this information created relevant geodatabases that led to a first draft predictive spatial distribution of coralligenous formations in the Mediterranean Sea using habitat suitability modelling techniques. In the last few decades, the use of hydroacoustics to map the seafloor for various geotechnical and habitat mapping projects accumulated high amounts of detailed spatial information about these formations, which remains majorly unexploited. Repurposing these datasets towards mapping key habitats is a valuable stepping stone to implementing the EU Habitat Directive. In Greece, a unique volume of seafloor mapping data has been gathered by the Laboratory of Marine Geology and Physical Oceanography, Geology Department, University of Patras. It accounts for more than 33 marine geophysical expeditions during the last three decades, having collected hydroacoustic data for a total seafloor area of 3,197.68 km2. In the present work, this information has been curated, re-evaluated, and archived to create the most complete, until now, atlas of coralligenous formations in the Greek Seas and the only integrating presence–absence data. This atlas has been used to train and validate a predictive distribution model, incorporating environmental variables derived from open data repositories, whose importance has been assessed and discussed. The final output is an improved probability map of coralligenous formation occurrence in the Greek Seas, which shall be the basis for effective spatial planning, gap detection, and design of future mapping and monitoring activities on this priority habitat.